2021
DOI: 10.1186/s13287-020-02070-2
|View full text |Cite|
|
Sign up to set email alerts
|

Mesenchymal stem cell-secreted prostaglandin E2 ameliorates acute liver failure via attenuation of cell death and regulation of macrophage polarization

Abstract: Background Acute liver failure (ALF) is an acute inflammatory liver disease with high mortality. Previous preclinical and clinical trials have confirmed that mesenchymal stem cell (MSC) is a promising therapeutic approach; however, the effect is not satisfied as the underlying molecular mechanisms of MSC in treating ALF remain unclear. Methods MSC isolated from 4- to 6-week-old C57BL/6 mice were used to treat ALF. Histological and serological param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 35 publications
2
54
0
1
Order By: Relevance
“…Interestingly, we also observed, for the first time, that HS pretreatment not only promoted the effects of MSCs in lung protection but also enhanced the potential of MSCs to modulate the NLRP3 inflammasome in macrophages. Wang et al proved that MSC-derived PGE2 inhibited TGF-β-activated kinase 1 (TAK1) signaling and NLRP3 inflammasome activation in liver macrophages to decrease the production of inflammatory cytokines [ 55 ]. Therefore, in this study, we measured the levels of cytokines secreted by MSCs to determine how HS pretreatment enhanced the therapeutic potential of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we also observed, for the first time, that HS pretreatment not only promoted the effects of MSCs in lung protection but also enhanced the potential of MSCs to modulate the NLRP3 inflammasome in macrophages. Wang et al proved that MSC-derived PGE2 inhibited TGF-β-activated kinase 1 (TAK1) signaling and NLRP3 inflammasome activation in liver macrophages to decrease the production of inflammatory cytokines [ 55 ]. Therefore, in this study, we measured the levels of cytokines secreted by MSCs to determine how HS pretreatment enhanced the therapeutic potential of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Nakajima and HongLong Zhou reported that MSCs can effectively improve spinal cord injury by polarizing macrophages from the M1 to M2 type (Nakajima et al, 2012;Zhou et al, 2016). Other studies have also reported that MSCs can alleviate liver diseases, such as acute liver injury and liver fibrosis, by inhibiting proinflammatory M1 cells and inducing M2 anti-inflammatory cells (Li C. et al, 2019;Wang et al, 2021). Reports also show that MSCs can improve diabetes by inducing macrophage polarization (Yin et al, 2018;Gao et al, 2019).…”
Section: Mscs Modulate the Macrophages Msc-mediated Effects On Macrophagesmentioning
confidence: 98%
“…This therapeutic potency was possibly mediated by MSC production of PGE2 to polarize M2 macrophages (Cao et al, 2020). Wang et al (2021) reported that MSCs can protect against D-galactosamine (D-Gal)-induced liver failure, and they found that MSCs regulate macrophage polarization by secreting PGE2. In addition, studies have reported that MSCs improve cardiac injury by increasing M2 macrophages through the COX-2-PGE2 pathway (Jin et al, 2019(Jin et al, , 2020.…”
Section: Pge2mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, inhibition of upstream PLA2 by dexamethasone [ 7 , 8 ] or downstream inducible PGE 2 synthase (mPGES-1) [ 9 ] confers protection as well. On the other, mesenchymal stem cell-derived PGE 2 [ 10 ] or PGE 2 signaling via EP 4 receptor [ 11 ] are claimed to exert hepatoprotective effects during liver injury.…”
Section: Introductionmentioning
confidence: 99%